SAT0676 (SERONEGATIVE) males show better eular treatment response than females in newly diagnosed rheumatoid arthritis (RA). (15th June 2017) - Yates, M; Galloway, J; Rivett, A; Norton, S; Ledingham, JM; Dennison, EM; Macgregor, AJ; Bechman, K; Rutherford, A; Snowden, N
Abstract : Background: Gender has been reported to play a role in attainment of RA remission (1), but the data are inconsistent. The impact of gender in early RA therefore warrants further investigation. Objectives: To assess the impact of gender on early RA outcomes. Methods: An audit, designed as a national prospective longitudinal observational study, was conducted to assess early RA care. All NHS providers in England and Wales were required to participate. Follow up data were captured over 3 months for subjects with a diagnosis of RA. Logistic regression was used to estimate associations between gender and DAS-28 response. Smoking status, baseline disease activity, age, antibody status, symptom duration, referral times, and treatment were considered in multivariate models. Results: 136 of 146 eligible trusts submitted data. 11, 752 subjects consented, 5, 622 were diagnosed with RA. DAS-28 response was available for 2234/5622 (39.7%). Male patients had a similar 3 month improvement in their DAS-28 to females, despite having a lower mean baseline score. Male gender associated with a higher rate of good EULAR response (DAS improvement >1.2, follow up DAS <3.3), with an adjusted odds ratio of 1.42 (CI 1.17–1.72). There were no differences between the genders in their treatment use or in other aspects of care including speed of referral (Table 1 ). The male excess in good EULAR response was more pronounced in seronegative compared with seropositive RA (1.98 (CI 1.4–2.8) compared to 1.21 (0.96–1.53)). Conclusions: The association of male gender with improved outcomes in early RA has not been shown before in a national cohort of this scope. Previous work suggests seronegative individuals achieve greater clinical response (2), here we present this effect amplified in men. To the authors' knowledge this is a new finding. This is likely multifactorial, with biological effect of gender, greater diagnostic uncertainty and higher reporting of global scores in women all potentially playing a role. References: Svensson B, Andersson M, Forslind K, Ajeganova S, Hafstrom I. Persistently active disease is common in patients with rheumatoid arthritis, particularly in women: a long-term inception cohort study. Scan rheum. 2016;45(6):448–55. Barra L, Pope JE, Orav JE, et al. Prognosis of seronegative patients in a large prospective cohort of patients with early inflammatory arthritis. Rheum. 2014;41(12):2361–9. Disclosure of Interest: None declared